Brief report of protective factors associated with family and parental well-being during the COVID-19 pandemic in an outpatient child and adolescent psychiatric clinic - Urban, Tamaki Hosoda; Friedman, Deborah; Kaskas, Maysa Marwan; Caruso, Alessandra J.; Canenguez, Katia M.; Rotter, Nancy; Wozniak, Janet; Basu, Archana (Frontiers in Psychology, 2022)
Families of children with mental health challenges may have been particularly vulnerable to emotional distress during the COVID-19 pandemic. This cross-sectional study surveyed 81 parents of children ages 6–17 years receiving mental health treatment in an outpatient clinic during the pandemic. We sought to characterize the impact of the pandemic on family relationships and parental well-being. Additionally, regression and ANCOVA models examined associations between four potentially protective factors – parents’ psychological resilience, perceived social support, positive family experiences during the pandemic, and children’s use of cognitive or behavioral coping strategies ¬– with family relationships and parental well-being. Findings suggest that families of children with mental health conditions experienced remarkable challenges to family relationships, parental well-being, and parents’ perceived capacity to support their children’s mental health. Nearly 80% of parents reported a negative impact of the pandemic on their own well-being, and 60% reported reduced ability to support their children’s mental health. Simultaneously, protective factors appeared to mitigate the negative impact of the pandemic. Particularly, support within the family (e.g., co-parenting) and from external sources (e.g., mental health services) were associated with better parents’ self-reported well-being for themselves and their capacity to support their children. Children’s use of coping tools, likely enhanced by mental health treatment, was also positively related to better family relationships and parental ability to support the child with mental health challenges. Our findings highlight the need for enhancing supports for families at multiple levels including individual skill-building, family-based/parenting support, and community-based support.